Urban transformation with TURAS open innovations; opportunities for transitioning through transdisciplinarity - Collier, Marcus (My University, 2016)
Transitioning is a unidirectional process of mainstreaming sustainability within normative societal behaviour, which communities hope will build resilience, reduce our dependence on distant resources and lead to the transformation towards more sustainable living as an end product. Throughout Europe there are numerous examples and pilot or demonstration projects that illustrate tools, practices, mechanisms, pathways and policies for how transitioning can be guided and a transformation can be achieved. This paper draws on the experience of the TURAS project by illustrating some of the diverse open innovation opportunities that have been derived using novel transdisciplinary approaches. The paper concludes with identifying possible ways forward by utilising the TURAS innovations to enable the transformation of urban communities.
Keywords: Sustainability; Urban transformation; Open innovation; Transdisciplinarity; smart cities; nature-based solutions; Smart & Sustainable Planet; INNOVATION; NATURE-BASED SOLUTIONS; Risk and resilience; Social Innovation; resilience; sustainability transitions; transdisciplinary collaboration; urban resilience